If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 = i + (-19) 1 = i + -19 Reorder the terms: 1 = -19 + i Solving 1 = -19 + i Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-1i' to each side of the equation. 1 + -1i = -19 + i + -1i Combine like terms: i + -1i = 0 1 + -1i = -19 + 0 1 + -1i = -19 Add '-1' to each side of the equation. 1 + -1 + -1i = -19 + -1 Combine like terms: 1 + -1 = 0 0 + -1i = -19 + -1 -1i = -19 + -1 Combine like terms: -19 + -1 = -20 -1i = -20 Divide each side by '-1'. i = 20 Simplifying i = 20
| 2x^2+10=100 | | 6y-11=4y+15 | | 3+3x=-2(1-x) | | 7x-1=2x+4 | | x^2+2x+12=180-x | | X^2+8x-23=o | | 4(x-3)=2x+10 | | 8j-6j-j=8 | | 5-5=-3x+2x | | 3.1+3.1x=x+16.7 | | 4w^2-13w-27=0 | | 8-2(2-3)=5(2) | | 6x-8x-11=-2x+3-11 | | .2(7+2t)=0.4t+1.4 | | .3f+9.4+.8f=-3.8 | | x^3=324 | | x^2+2x+191=0 | | 6(e+4)=4c+-18 | | x+3+x+4+x=60 | | y+8=-53 | | 7u^2-4u-3=0 | | 1-(-1/4)= | | -3x-9x=96 | | x+2+x+3.5+x=60 | | -4(3+z)+6z-12=-36 | | (27x-6y)+4(9y-5x)= | | 3x^2+2kx+k-1=0 | | 5t-13t=-32 | | 3g-g-1=17 | | x+2+x+3+x=60 | | b=5mx+6y | | 3(2x-1)=3(6x+3) |